If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -4x = 21 + -6x Solving 13 + -4x = 21 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 13 + -4x + 6x = 21 + -6x + 6x Combine like terms: -4x + 6x = 2x 13 + 2x = 21 + -6x + 6x Combine like terms: -6x + 6x = 0 13 + 2x = 21 + 0 13 + 2x = 21 Add '-13' to each side of the equation. 13 + -13 + 2x = 21 + -13 Combine like terms: 13 + -13 = 0 0 + 2x = 21 + -13 2x = 21 + -13 Combine like terms: 21 + -13 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 8f+19=14 | | 0=3x^2+13x+4 | | (1+v)(5v+7)=0 | | -3(r+6)=-41 | | 3x-7-7x=5 | | f(x)=3cosx | | 5.3=9.3-0.5x | | 0=20t-4.9t^2 | | x/6=12/15 | | 2(2x-i)4x-6x= | | 4a+2b-6a+3a= | | 37.12=8g+3.84 | | (x-8)2/3=4 | | 5y+30=3x | | 3x-6/4=12 | | v^2-2v-5=0 | | 545/5 | | y/0.5=-6 | | 2x+(-3)=9 | | log(x+6)-log(6)=log(12) | | ln(3x)=x-4 | | y/.5=-6 | | 2ln(x+4)=4 | | -(7-8A)-(2+7A)-27=-(3-7A)+(-A)+2 | | 2(2x-i)-4x-6x= | | 5*3/5x-5*6 | | 9x^4-18x^2+5=0 | | 4r^3=72 | | 1/2x2/7= | | 4c=54 | | 1.3x+2.1=5.7 | | 24+4b=8 |